IN DEFENSE OF THE SOCIAL SAFETY NET. Issue 38 (30th September 2014) - Duncan, Craig
<x content-type="archive" xml:space="preserve">Abstract</x> This article responds to Tibor Machan's criticisms of government provision for needy citizens. It argues that although charity may be morally worthy, private charity is inadequate to the task of providing our fellow citizens with the security they deserve; the tremendous social good of secure access to a life of dignity can only be produced by a public social safety net. Moreover, individual rights to property do not stand in the way of providing a public social safety net. Since there are social inputs in wealth creation, reasonable levels of taxation do not violate people's rights to their wealth.